Load Compensation By Using Three-Phases Three-Level Cascaded Inverter Based D-Statcom - Coteli, Resul; Deniz, Erkan; Dandil, Besir; Tuncer, Servet (Gazi Univ, 2010)
Reactive power compensation is a necessity for decreasing the losses in transmission and distribution lines, reducing the manufacturing cost and more quality energy to customers. In recent years, studies depending on advances in semiconductor technology showed that voltage collapse in the power systems can be prevented and dynamic stability in the power systems can be improved if reactive power compensation is done with semiconductors. In this paper, three-phase 3-level cascade inverter based on D-STATCOM of +/- 25kVAR connected to secondary of distribution transformer is simulated for purpose of load compensation. For this aim, distribution system, D-STATCOM and control unit are modelled with MATLAB/Simulink ve Simpower Systems and D-STATCOM's performance for load compensation is investigated in terms of switching on/off inductive and capacitive loads that they have different power values.
Keywords: D-STATCOM; Load Compensation; Three-Level Cascade Inverter